The study of intestinal toxicity induced by gossypol acetic acid and the mechanism using zebrafish model and network toxicology - Hanxue Zhao; Yuxin Wang; Guoliang Zhang; Yudi Jing; Fangzhen Li; Xiqiang Chen; Kechun Liu; Guiling Chen; Rongchun Wang (Toxicology and Applied Pharmacology, 2026)

Transcriptomics analysis elucidates the growth inhibitory mechanisms of volatile fungistatic compound 3-ethylbenzaldehyde to Pseudocryphonectria elaeocarpicola - Yuchen Yang; Guiling Ran; Haoyu Wu; Liangji Li; Dianguang Xiong; Huayi Huang; Chengming Tian (Pesticide Biochemistry and Physiology, 2026)

Enhanced glyphosate biodegradation by heavy metal-tolerant microbial consortium QLBS in co-contaminated environment: Kinetics and metabolic pathways - Zeren Li; Mengyi Chen; Ziye Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Haoran Song; Huijie Zhou; Zhenyu Zhang; Bin Liang; Sandhya Mishra; Mohamed A. Ghorab; et al. (Journal of Cleaner Production, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Ultrasensitive and selective detection of metronidazole residues in milk powder using a novel 3D MOF fluorescent sensor - Xuanqi Zhang; Guiling Gao; Xiaoyong Lai; Qin Hou; Yi Li; Zhiyong Teng; Xiaozhong Wang; Xiao Zhang; Qingfeng Yang (Food Chemistry, 2026)

Construction of 3D printed self-supporting electrode for efficient electrochemical lithium recovery from brine - Muyao He; Guiling Luo; Li Zhang; Jun Gu; Tongyu Wu; Xiaoxiao Yu; Minmeng Tang; Xiao Zhang; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2026)

Baculovirus manipulation of nutrient-based host choice via an infection responsive olfactory receptor in Spodoptera exigua - Zaiyuan Li; Xin Gao; Qihong Ma; Lianhai Fu; Changyou Li; Yan Shi; Jie Li; Qianlong Yu; Guiling Zheng; Chunhong Yang; Fanghao Wan; Wanqiang Qian; et al. (Pesticide Biochemistry and Physiology, 2026)

Physical exercise protects cardiovascular fitness in long-term spaceflight: what have we learned? - Zi’ang Zhang; Wenjuan Xing; Guiling Wu; Xing Zhang; Jia Li; Yingxian Li; Feng Gao (Science China Life Sciences, 2026)

Environmental factors shape the intestinal microbiota and function of Manila clam Ruditapes philippinarum - Bifu Gan; Guiling Li; Yanru Xu; Jingmiao Yang; Weilang Lin; Xiaobo Yan; Maozi Lin; Guangmao Ding; Fang Su; Qizhen Xiao (Frontiers in Marine Science, 2026)
Intestinal microbiota of aquatic animals is closely associated with the environment, influencing their health, immune defense, and environmental adaptability. To understand the relationships among the Manila clam ( Ruditapes philippinarum ) intestinal microbiota, the bacterial communities in their habitats, and environmental factors, as well as the characteristics and potential functions of the intestinal microbiota. This study systematically analyzed the bacterial communities in the clam intestines, seawater, and sediment samples from two typical habitats using 16S rRNA gene (V3-V4) sequencing. The results revealed significant differences in bacterial community composition among the intestines, seawater and sediment, with pronounced regional variations also evident within the same sample type. The clams gut microbiota in Fuqing was predominantly composed of Alphaproteobacteria , Gammaproteobacteria , Bacteroidota , Bacillota , and Cyanobacteria . In Putian, Cyanobacteria comprised an exceptionally high proportion. However, Bacillota , Bacteroidota , and Actinomycetota showed similar relative abundances in both regions, indicating a potential “core bacterial community”. Regarding the α-diversity of gut microbiota, although no significant differences were observed between clam samples from the two regions, their diversity was significantly lower than that of the sediment bacterial communities. The intestinal bacterial communities exhibited high similarity to the aquatic bacterial communities in terms of richness, diversity, and dominant species abundance, and it shares most of the ASVs with the sediment, suggesting that environmental microorganisms may serve as the primary source of the clam intestinal microbiota. Environmental drivers of bacterial communities differed regionally. In Fuqing, bacterial communities were associated with temperature, DO, pH, and salinity, and exhibited broader niche widths; in Putian, they were mainly influenced by nutrients, showing narrower niches. Compared to bacterial networks in the environment, the interactions among members within the gut bacterial communities of clams display modularity, indicative of functional specialization. The composition and functions of the intestinal microbiota of clams vary significantly in different environments, which may be a manifestation of their ecological adaptability. The composition and function of clam intestinal microbiota varied with environment, reflecting their ecological adaptability. These findings provide a scientific theoretical basis for water quality regulation and disease prevention in aquatic animal farming operations.

ETV5 upregulates PD-L1 transcription to inhibit cytotoxic CD8+ T cell proliferation in colorectal cancer - Fei Kuang; Zhongwen Hu; Longtao Huangfu; Guiling Yan; Swati Dhiman; Wenzheng Chen; Ziyu Li (Science China Life Sciences, 2026)

Covalently bonded amino-functionalized ZIF-8 on Cu2O for photocatalytic reduction of low-concentration CO2 - Jinke Li; Zhenbo Zhang; Guiling Liu; Hao Shi; Jingru Wang; Jiayi Wan; Tong Bian; Huijun Yu (Chemical Engineering Journal, 2026)

Differences in Volatile Composition and Expression of Genes Involved in Terpenes Biosynthesis in Hemerocallis Species - Wenjie Gao; Yuyang Li; Xingran Kou; Qinfei Ke; Feng Chen; Guiling Liu; Qingran Meng (Journal of Plant Growth Regulation, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Research on the mechanism of acidizing the carbonate Gaoyuzhuang Reservoir, North China: Insights from field experiments and numerical simulations - Gaofan Yue; Guiling Wang; Feng Ma; Xi Zhu; Xiaoyuan Li (Geothermics, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Fibroblast Growth Factor 8 Suppresses Neurotoxic Astrocytes and Alleviates Neuropathic Pain via Spinal FGFR3 Signaling - Huizhu Liu; Lanxing Yi; Guiling Li; Kangli Wang; Hongsheng Wang; Yuqiu Zhang; Benlong Liu (Neuroscience Bulletin, 2025)
Astrocytes in the spinal dorsal horn (SDH) exhibit diverse reactive phenotypes under neuropathic conditions, yet the mechanisms driving this diversity and its implications in chronic pain remain unclear. Here, we report that spared nerve injury (SNI) induces marked upregulation of both complement component 3 (C3⁺, A1-like) and S100 calcium-binding protein A10 (S100A10⁺, A2-like) astrocyte subpopulations in the SDH, with elevated microglial cytokines including interleukin-1α, tumor necrosis factor-α, and complement component 1q. Transcriptomic, immunohistochemical, and Western blot analyses reveal co-activation of multiple reactive astrocyte states over a unidirectional shift toward an A1-like phenotype. Fibroblast growth factor 8 (FGF8), a neuroprotective factor via FGFR3, mitigated microglia-induced C3⁺ astrocyte reactivity in vitro and suppressed spinal C3 expression and mechanical allodynia following intrathecal administration in SNI mice. These findings reveal a microglia–astrocyte signaling axis that promotes A1 reactivity and position FGF8 as a promising therapeutic candidate for neuropathic pain by modulating astrocyte heterogeneity.

Study on the pore structure evolution of granodiorite after cyclic thermal shock - Shutao Zhou; Qiang Sun; Guiling Wang; Xiting Long; Jianjun Hu; Tingxin Li (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

An SNP for the splice donor variant of i-type lysozyme 2 (lyz-i2) is associated with the resistance of Vibrio harveyi in Pacific white shrimp - Xin Zhang; Peng Luo; Chunhua Ren; Pengying Li; Yehui Tan; Hao Yang; Shuyang Wen; Bo Ma; Jiayue Yin; Yanhong Wang; Xiao Jiang; Jingxuan Liang; et al. (Aquaculture, 2025)

Raindrop size distribution characteristics of summer and autumn tropical cyclones in the South China Sea based on satellite observations - Guiling Qian; Jiangnan Li; Jianfei Chen (Dynamics of Atmospheres and Oceans, 2025)

Accordion-structured robust zinc anodes via MXene-guided deposition towards durable zinc-ion batteries - Yiyang Mao; Zhuo Li; Qidi Zhang; Qi Fan; Yuao Wang; Jing Zhao; Guiling Wang; Dianxue Cao; Kun Liang; Kai Zhu (Chemical Engineering Journal, 2025)

C22-Ceramide Derived from Marine Microalgae Emiliania huxleyi Induces Melanosomal Autophagy via JNK/c-Jun Signaling Pathway in Mouse B16 Melanoma Cells - Jiyue Wan; Hui Ma; Yuxuan Xu; Shumiao Zhang; Jian Li; Guiling Li; Shiying Huang; Xiaotong Ye; Zhengxiao Zhang; Jingwen Liu (Journal of Ocean University of China, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Genetically engineered Bacillus subtilis-derived extracellular vesicles Alleviates Ulcerative colitis by restoring intestinal barrier and regulating gut microbiota - Jiali Chen; Chaozhi Wei; Chunqiang Pan; You Wei; Baoxian Li; Tao Liu; Xiao Wang; Zhengshun Wen; Yao Zhao; Mengyu Zhang; Jintao Cheng; Yuanxiang Jin; et al. (Chemical Engineering Journal, 2025)

Role of Natural Discontinuities in Fracture Propagation in Hot Dry Rock: Observations and Implications from the Field Injection Test - Jingyu Xie; Zhengguang Zhao; Lei Li; Hao Zhang; Jing Zheng; Wei Qiao; Chongyuan Zhang; Suping Peng; Guiling Wang; Dan Wang; Xianpeng Jin (Rock Mechanics and Rock Engineering, 2025)

Evaluating the effects of intrinsic and isolated arabinoxylans on human gut microbiota and short-chain fatty acids: A systematic review and meta-analysis - Changcan Feng; Chenxi Cai; Edward C. Deehan; Shanshan Jiang; Mingyue Yang; Zhongming Weng; Jiahui Long; Guiling Li; Jian Li; Jingwen Liu; Zhengxiao Zhang (Trends in Food Science & Technology, 2025)

Regulation and response of heterotrophic bacterial production to environmental changes in marginal seas of the Western Pacific Ocean - Qiao Liu; Jinyan Wang; Xiao-Jun Li; Ni Meng; Gui-Peng Yang; Guiling Zhang; Guang-Chao Zhuang (Global and Planetary Change, 2025)

Effects of light intensity and light duration on growth performance and ovarian development in red swamp crayfish Procambarus clarkii (Girard, 1852) - Long Wang; Meng Hu; Lin Cai; Yurui Wang; Tianyu Guan; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Aquaculture International, 2025)

Removal of alachlor from the water/soil environments: The significance of microbial remediation and its biochemical mechanisms - Zeren Li; Mengyi Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Water Process Engineering, 2024)

Refining water and carbon fluxes modeling in terrestrial ecosystems via plant hydraulics integration - Shanshan Sun; Lingcheng Li; Zong-Liang Yang; Guiling Wang; Nate G. McDowell; Ashley M. Matheny; Jian Wu; Shiqin Xu; Hui Zheng; Miao Yu; Dagang Wang (Agricultural and Forest Meteorology, 2024)

Three dietary phenols from pickled radish improve uric acid metabolism disorder in hyperuricemia mice associated with the altered gut microbiota composition - Xiaoze Liu; Lingyu Zhang; Daren Wu; Jingwen Liu; Guiling Li; Zhengxiao Zhang; Jian Li (Food Bioscience, 2024)

Multistage regulation of LiMn2O4 electrode for electrochemical lithium extraction from salt-lake - Jun Gu; Linlin Chen; Linjing Fan; Guiling Luo; Xiaowei Li; Xiaojun Chen; Haiyan Ji; Yanhong Chao; Wenshuai Zhu (Desalination, 2024)

Hydrogeochemistry of geothermal water in Huangshadong and adjacent areas of Guangdong province: Implications for water-rock interaction - Lu Liu; Guiling Wang; Yalu Li; Zhengan Wei; Wenjing Lin; Xianan Qin; Min Zhang; Shihua Qi; Xiting Long (Geothermics, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Preparation and identification of antioxidant peptides from Quasipaa spinosa skin through two-step enzymatic hydrolysis and molecular simulation - Daren Wu; Yuanhao Cao; Dejin Su; Emad Karrar; Lingyu Zhang; Chaoxiang Chen; Ning Deng; Zhengxiao Zhang; Jingwen Liu; Guiling Li; Jian Li (Food Chemistry, 2024)

Toxic mechanisms of nanoplastics exposure at environmental concentrations on juvenile red swamp crayfish (Procambarus clarkii): From multiple perspectives - Long Wang; Qianqian Zhu; Meng Hu; Xinyi Zhou; Tianyu Guan; Nan Wu; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Environmental Pollution, 2024)

Soil water dynamics and deep percolation in an agricultural experimental area of the North China Plain over the past 50 years: Based on field monitoring and numerical modeling - Yanyan Wang; Yujiang He; Zhiping Li; Jihong Qu; Guiling Wang (Science of The Total Environment, 2024)

Ecological transitions in Xinjiang, China: Unraveling the impact of climate change on vegetation dynamics (1990–2020) - Haichao Hao; Junqiang Yao; Yaning Chen; Jianhua Xu; Zhi Li; Weili Duan; Sadaf Ismail; Guiling Wang (Journal of Geographical Sciences, 2024)

Absorption and utilization of polysaccharides from Cordyceps militaris fruiting bodies and their protective effects against CCl4-induced acute liver injury in mice - Lin Lan; Jingxin Wang; Hao Luo; Min Cao; Nianhong Guo; Guiling Fan; Shengyu Wang; Zaixing Sun; QiaoLing He; Yufeng Li (Food Bioscience, 2024)

Structure-activity relationships of antimicrobial phenolic derivatives from Phyllanthus emblica against Streptomyces scabies - Xiuna Wu; Daren Wu; Jiahao Yuan; Lingyu Zhang; Jingwen Liu; Guiling Li; Li Wang; Jian Li (Food Bioscience, 2024)

Selective extraction of lithium ions by phosphoroxy-functionalized ionogels from the mother liquor of Li2CO3 - Yuhong Huang; Xiaowei Li; Guiling Luo; Duanjian Tao; Linlin Chen; Jing Sun; Bizuneh Kaleab; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2024)

High-directional thermally conductive stearic acid/expanded graphite - Graphene films for efficient photothermal energy storage - Zhaofeng Dai; Guiling Zhang; Yufei Xiao; Yulong Ding; Yongliang Li; Xiaohui She; Xiaosong Zhang; Dongliang Zhao (Chemical Engineering Journal, 2024)

The spatial patterns and driving mechanisms of blue carbon ‘loss’ and ‘gain’ in a typical mangrove ecosystem: A case study of Beihai, Guangxi Province of China - Zhenxi Xie; Haonan Li; Yuan Yuan; Wei Hu; Gang Luo; Longtian Huang; Mo Chen; Weimei Wu; Guiling Yan; Xiang Sun (Science of The Total Environment, 2023)

Identification of flavonoids in Anoectochilus roxburghii and in vitro inhibition of key enzymes relevant to metabolic syndrome - Jiahao Yuan; Xiuna Wu; Emad Karrar; Lingyu Zhang; Jingwen Liu; Guiling Li; Chaoxiang Chen; Zhengxiao Zhang; Daren Wu; Jian Li (Food Bioscience, 2023)

Deep structure of the Rongcheng geothermal field, Xiongan New Area: Constraints from resistivity data and boreholes - Yunqi Zhu; Diquan Li; Yanfang Hu; Xian Zhang; Fu Li; Feng Ma; Guiling Wang (Geothermics, 2023)

Stress estimation in a 3 km-deep geothermal borehole: A snapshot of stress state in Southern Cathaysia block, China - Chongyuan Zhang; Bin Li; Hailong Li; Manchao He; Haonan Gan; Guiling Wang; Yanxia Fan (Tectonophysics, 2023)

Composition and localization of the leaf waxes in seven epiphytic Tillandsia species - Guiling Zheng; Peng Li (Biochemical Systematics and Ecology, 2023)

Study on the Role of Mitophagy Receptor PHB2 in Doubly Uniparental Inheritance of Hyriopsis cumingii - Yayu Wang; Xiaoyue Zhu; Yang Gu; Zongyu Liu; Yingrui Mao; Xiaojun Liu; Zhiyi Bai; Guiling Wang; Jiale Li (Marine Biotechnology, 2023)

Urban rainfall-runoff flooding response for development activities in new urbanized areas based on a novel distributed coupled model - Donglai Li; Jingming Hou; Qingshi Zhou; Jiahao Lyu; Zhanpeng Pan; Tian Wang; Xueliang Sun; Guiling Yu; Junyan Tang (Urban Climate, 2023)

Hormesis in the heavy metal accumulator plant Tillandsia ionantha under Cd exposure: Frequency and function of different biomarkers - Jingyi Zhang; Zhen Tang; Evgenios Agathokleous; Guiling Zheng; Liang Xu; Peng Li (Science of The Total Environment, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Effects of copper on gill function of juvenile oriental river prawn (Macrobrachium nipponense): Stress and toxic mechanism - Long Wang; Tianyu Guan; Guiling Wang; Jieyi Gu; Nan Wu; Chuankun Zhu; Hui Wang; Jiale Li (Aquatic Toxicology, 2023)

Characterization of the sphingolipid profiling of Emiliania huxleyi against virus infection - Jingwen Liu; Jingjing Gao; Enquan Zhang; Hanrui Jiang; Guiling Li; Jian Li; Jun Zeng; Daren Wu (Journal of Oceanology and Limnology, 2023)

A Responsive Feeding Questionnaire Based on Self-Determination Theory for Caregivers of Chinese Toddlers - Yan Liu; Guiling Yu; Zhihui Li; Yan Kong; Rui Yang; Chunlan Yin; Xiaodi Sun (Journal of Nutrition Education and Behavior, 2023)

Larger bees facilitate the deposition of oilseed rape pollen (Brassica napus L.) - Hongcai Chang; Zhijun Wei; Ran Liu; Guiling Ding; Jun Li; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2023)

Geochemical processes and indicative significance of rare earth elements in high arsenic geothermal fluids in Batang, western Sichuan, China - wei Zhang; hanxiong Zhang; guiling Wang; jiayi Zhao; gaofan Yue; man Li; shuaichao Wei; zewei Qu (Geothermics, 2023)

Tacrolimus improved the pregnancy outcomes of patients with refractory recurrent spontaneous abortion and immune bias disorders: a randomized controlled trial - Juan Liu; Meiqin Li; Jinhua Fu; Guiling Yuan; Ning Li; Yinghui Fu; Long Zhao (European Journal of Clinical Pharmacology, 2023)

Breaking intramolecular hydrogen bonds of polymer films to enable dendrite-free and hydrogen-suppressed zinc metal anode - Yiyang Mao; Zhuo Li; Yiju Li; Dianxue Cao; Guiling Wang; Kai Zhu; Guohua Chen (Chemical Engineering Journal, 2023)

Electrochemical lithium ion pumps for lithium recovery: A systematic review and influencing factors analysis - Guiling Luo; Xiaowei Li; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Desalination, 2023)

Preparation of high hydrophilic H2TiO3 ion sieve for lithium recovery from liquid lithium resources - Jing Sun; Xiaowei Li; Yuhong Huang; Guiling Luo; Duanjian Tao; Jiangtao Yu; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2023)

Shifts in plant and soil C, N, and P concentrations and C:N:P stoichiometry associated with environmental factors in alpine marshy wetlands in West China - Guiling Wu; Jay Gao; Honglin Li; Fei Ren; Defei Liang; Xilai Li (CATENA, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Structural and functional alterations within the Papez circuit in subacute stroke patients - Su Yan; Yuanhao Li; Jun Lu; Tian Tian; Guiling Zhang; Yiran Zhou; Di Wu; Shun Zhang; Wenzhen Zhu (Brain Imaging and Behavior, 2022)

Examining key impact factors of energy-related carbon emissions in 66 Belt and Road Initiative countries - Chuanhe Xiong; Guiling Wang; Hengpeng Li; Weizhong Su; Xuejun Duan (Environmental Science and Pollution Research, 2022)

The Duration and Determinants of Anti-SARS-CoV-2 Immunoglobulin G in Cancer Patients with SARS-CoV-2 Infection: A Longitudinal Study - Yao Jiang; Yingchao Zhao; Guiling Li (Current Microbiology, 2022)
Patients with cancer have an increased risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and a high case-fatality rate. The duration of anti-SARS-CoV-2 immunoglobulin G (IgG) antibodies in cancer patients following SARS-CoV-2 infection has not been reported previously. We conducted a longitudinal study at a cancer center in Wuhan, China to determine the duration of the humoral immune response following SARS-CoV-2 infection in cancer patients and to determine factors associated with a short duration (< 6 months) of anti-SARS-CoV-2 immunoglobulin G (IgG). Of 2139 cancer patients screened, 78 with confirmed SARS-CoV-2 infection were included in this study. SARS-CoV-2 IgG antibodies were present for < 6 months in 39.7% of these patients. In addition, patients who received chemotherapy were more likely to have a short duration of anti-SARS-CoV-2 IgG (odds ratio 5.31, 95% confidence interval 1.09–26.02, P < 0.05). Our study suggests that cancer patients, especially those who were receiving chemotherapy, have a shorter anti-SARS-CoV-2 IgG duration following infection and therefore, should be prioritized for vaccination.

A New Method for Detection African Swine Fever Virus: Time-resolved Fluorescence Immunoassay - Cuicui Chen; Hongrui Lai; Huankun Liang; Ying He; Guiling Guo; Laiqing Li (Journal of Fluorescence, 2021)

LncRNA NEAT1 contributes to the acquisition of a tumor like-phenotype induced by PM 2.5 in lung bronchial epithelial cells via HIF-1α activation - Pan Jiang; Shengyu Hao; Liang Xie; Guiling Xiang; Weiping Hu; Qinhan Wu; Zilong Liu; Shanqun Li (Environmental Science and Pollution Research, 2021)

Flavonoids improve drought tolerance of maize seedlings by regulating the homeostasis of reactive oxygen species - Baozhu Li; Ruonan Fan; Guiling Sun; Ting Sun; Yanting Fan; Shenglong Bai; Siyi Guo; Shiquan Huang; Jiong Liu; Hui Zhang; Pengtao Wang; Xiaohong Zhu; et al. (Plant and Soil, 2021)
Background and aims As drought threatens the yield and quality of maize ( Zea mays L.), it is important to dissect the molecular basis of maize drought tolerance. Flavonoids, participate in the scavenging of oxygen free radicals and alleviate stress-induced oxidative damages. This study aims to dissect the function of flavonoids in the improvement of maize drought tolerance. Methods Using far-infrared imaging screening, we previously isolated a drought overly insensitivity ( doi ) mutant from an ethyl methanesulfonate (EMS)-mutagenized maize library and designated it as doi57 . In this study, we performed a physiological characterization and transcriptome profiling of doi57 in comparison to corresponding wild-type B73 under drought stress. Results Under drought stress, doi57 seedlings displayed lower leaf-surface temperature (LST), faster water loss, and better performance in growth than B73. Transcriptome analysis reveals that key genes involved in flavonoid biosynthesis are enriched among differentially expressed genes in doi57 . In line with these results, more flavonols and less hydrogen peroxide (H 2 O 2 ) were accumulated in guard cells of doi57 than in those of B73 with the decrease of soil water content (SWC). Moreover, the capacity determined from doi57 seedling extracts to scavenge oxygen free radicals was more effective than that of B73 under the drought treatment. Additionally, doi57 seedlings had higher photosynthetic rates, stomatal conductance, transpiration rates, and water use efficiency than B73 exposed to drought stress, resulting in high biomass and greater root/shoot ratios in doi57 mutant plants. Conclusion Flavonoids may facilitate maize seedling drought tolerance by lowering drought-induced oxidative damage as well regulating stomatal movement.

Transformation of coccolithophorid Emiliania huxleyi harboring a marine virus (Coccolithoviruses) serine palmitoyltransferase (SPT) gene by electroporation - Weicong Cai; Xueting Wang; Jinjing Su; Jian Li; Jun Zeng; Guiling Li; Jingwen Liu (Journal of Oceanology and Limnology, 2021)

Combined toxic impacts of thiamethoxam and four pesticides on the rare minnow (Gobiocypris rarus) - Guiling Yang; Lu Lv; Shanshan Di; Xinfang Li; Hongbiao Weng; Xinquan Wang; Yanhua Wang (Environmental Science and Pollution Research, 2021)

Impact of histaminergic H3 receptor antagonist on hypoglossal nucleus in chronic intermittent hypoxia conditions - Liang Xie; Qinhan Wu; Weiping Hu; Xu Wu; Guiling Xiang; Shengyu Hao; Han Guo; Shanqun Li (Psychopharmacology, 2021)

MicroRNAs in the Spinal Microglia Serve Critical Roles in Neuropathic Pain - Simin Tang; Huan Jing; Fuhu Song; Haicheng Huang; Wenjun Li; Guiling Xie; Jun Zhou (Molecular Neurobiology, 2021)

Toxicological interactions of cadmium and four pesticides on early life stage of rare minnow (Gobiocypris rarus) - Yanhua Wang; Xinfang Li; Chao Xu; Guiling Yang; Dou Wang; Xinquan Wang; Qiang Wang (Ecotoxicology, 2020)

Variations in Dissolved Methane in the Yellow Sea During the Spring Algal Blooms of 2009 - Wangwang Ye; Guiling Zhang; Peipei Li; Feng Zhou; Chenggang Liu (Journal of Ocean University of China, 2019)

Resuspension of settled atmospheric particulate matter on plant leaves determined by wind and leaf surface characteristics - Guiling Zheng; Peng Li (Environmental Science and Pollution Research, 2019)

Virus-induced apoptosis and phosphorylation form of metacaspase in the marine coccolithophorid Emiliania huxleyi - Jingwen Liu; Weicong Cai; Xian Fang; Xueting Wang; Guiling Li (Archives of Microbiology, 2018)

Influence of a water regulation event on the age of Yellow River water in the Bohai - Zhen Li; Haiyan Wang; Xinyu Guo; Zhe Liu; Huiwang Gao; Guiling Zhang (Journal of Ocean University of China, 2017)

The regional impact of Land-Use Land-cover Change (LULCC) over West Africa from an ensemble of global climate models under the auspices of the WAMME2 project - Aaron Anthony Boone; Yongkang Xue; Fernando De Sales; Ruth E. Comer; Samson Hagos; Sarith Mahanama; Kathleen Schiro; Guoqiong Song; Guiling Wang; S. Li; Carlos R. Mechoso (Climate Dynamics, 2016)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

SIRT1 activation by pterostilbene attenuates the skeletal muscle oxidative stress injury and mitochondrial dysfunction induced by ischemia reperfusion injury - Yedong Cheng; Shouyin Di; Chongxi Fan; Liping Cai; Chao Gao; Peng Jiang; Wei Hu; Zhiqiang Ma; Shuai Jiang; Yushu Dong; Tian Li; Guiling Wu; et al. (Apoptosis, 2016)

HO-1 Signaling Activation by Pterostilbene Treatment Attenuates Mitochondrial Oxidative Damage Induced by Cerebral Ischemia Reperfusion Injury - Yang Yang; Jiayi Wang; Yue Li; Chongxi Fan; Shuai Jiang; Lei Zhao; Shouyin Di; Zhenlong Xin; Bodong Wang; Guiling Wu; Xia Li; Zhiqing Li; et al. (Molecular Neurobiology, 2016)

Multi-functional Liposomes Enhancing Target and Antibacterial Immunity for Antimicrobial and Anti-Biofilm Against Methicillin-Resistant Staphylococcus aureus - Yansha Meng; Xucheng Hou; Jiongxi Lei; Mengmeng Chen; Shuangchen Cong; Yuanyuan Zhang; Weiming Ding; Guiling Li; Xinru Li (Pharmaceutical Research, 2016)

Activation of endoplasmic reticulum stress is involved in the activity of icariin against human lung adenocarcinoma cells - Shouyin Di; Chongxi Fan; Yang Yang; Shuai Jiang; Miaomiao Liang; Guiling Wu; Bodong Wang; Zhenlong Xin; Wei Hu; Yifang Zhu; Weimiao Li; Yongan Zhou; et al. (Apoptosis, 2015)

Bayesian Markov Chain Random Field Cosimulation for Improving Land Cover Classification Accuracy - Weidong Li; Chuanrong Zhang; Michael R. Willig; Dipak K. Dey; Guiling Wang; Liangzhi You (Mathematical Geosciences, 2015)

Gene expression pattern of insect fat body cells from in vitro challenge to cell line establishment - Huan Zhang; Qian Meng; Ping Tang; Xuan Li; Wei Zhu; Guiling Zhou; Ruihao Shu; Jihong Zhang; Qilian Qin (In Vitro Cellular & Developmental Biology - Animal, 2014)

Comparative analysis of total carotenoid content in tissues of purple and white inner-shell color pearl mussel, Hyriopsis cumingii - Xilei Li; Zhiyi Bai; Hongrui Luo; Guiling Wang; Jiale Li (Aquaculture International, 2014)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)

A new insect cell line from the pupal ovary of the Asian corn borer moth Ostrinia furnacalis - Ning Zhang; Qilian Qin; Huan Gong; Qian Meng; Wei Zhu; Menglong Wang; Jihong Zhang; Guiling Zhou; Xuan Li; Huan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2014)

Comparison of growth and pearl production in males and females of the freshwater mussel, Hyriopsis cumingii, in China - Yongchao Zhao; Zhiyi Bai; Longlong Fu; Yue Liu; Guiling Wang; Jiale Li (Aquaculture International, 2013)

Analysis on cDNA sequence, alternative splicing and polymorphisms associated with timing of puberty of Lin28B gene in goats - Guiling Cao; Qiuyue Liu; Mingxing Chu; Ran Di; Li Fang; Tao Feng; Ning Li (Molecular Biology Reports, 2013)

Isolation and characterization of ten microsatellite markers of Fenneropenaeus penicillatus - Yuanyu Cao; Zhongbao Li; Guiling Zhang; Xiaojiao Chen; Lina Chen; Qinghui Li (Conservation Genetics Resources, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

Molecular cytogenetic identification of a novel dwarf wheat line with introgressed Thinopyrum ponticum chromatin - Guiling Chen; Qi Zheng; Yinguang Bao; Shubing Liu; Honggang Wang; Xingfeng Li (Journal of Biosciences, 2012)

Characterization of the Hormone and Stress-Induced Expression of FaRE1 Retrotransposon Promoter in Strawberry - Ping He; Yue Ma; Hongyan Dai; Linguang Li; Yuexue Liu; He Li; Guiling Zhao; Zhihong Zhang (Journal of Plant Biology, 2012)

Polymorphisms of coding region of BMPR-IB gene and their relationship with litter size in sheep - Mingxing Chu; Lihua Jia; Yingjie Zhang; Mei Jin; Hongquan Chen; Li Fang; Ran Di; Guiling Cao; Tao Feng; Qianqian Tang; Yuehui Ma; Kui Li (Molecular Biology Reports, 2011)

Integrating miRNA and mRNA expression profiles in response to heat stress-induced injury in rat small intestine - Jin Yu; Fenghua Liu; Peng Yin; Xiaoyu Zhu; Guiling Cheng; Nin Wang; An Lu; Weili Luan; Nuowei Zhang; Jiefeng Li; Kaijun Guo; Yulong Yin; et al. (Functional & Integrative Genomics, 2011)

FaRE1: a transcriptionally active Ty1-copia retrotransposon in strawberry - Ping He; Yue Ma; Guiling Zhao; Hongyan Dai; He Li; Linlin Chang; Zhihong Zhang (Journal of Plant Research, 2010)

Identification of Genes Involved in Immune Response, Microsatellite, and SNP Markers from Expressed Sequence Tags Generated from Hemocytes of Freshwater Pearl Mussel (Hyriopsis cumingii) - Zhiyi Bai; Yuxin Yin; Songnian Hu; Guiling Wang; Xiaowei Zhang; Jiale Li (Marine Biotechnology, 2009)

Isolation and characterization of genomic retrotransposon sequences from octoploid strawberry (Fragaria × ananassa Duch.) - Yue Ma; Haiyue Sun; Guiling Zhao; Hongyan Dai; Xiuyan Gao; He Li; Zhihong Zhang (Plant Cell Reports, 2008)